DYNAMIC CAPABILITIES DALAM DEMOKRATISASI PELAYANAN PUBLIK DI INDONESIA PADA MASA PANDEMI COVID-19 - Resa Vio Vani (Universitas Halu Oleo, 2021)
Coronavirus disease 2019 is a major disaster for apathy bureaucracy, so the government is required to be able to provide public services in limited interactions. Therefore, the dynamic governance ability shown in this study aims to reveal public expectations in public services during Covid-19 through policy, and to understand the realization of objectives that must be fully understood. As well as how the democratization of public services should be the road to service excellent seen based on the theory of dynamic capabilities that are part of dynamic governance, where able people and agile processes become the benchmark of good implementation of public services, using 3 indicators namely Thinking Ahead, Thinking Again, and Thinking Across. all this is a process towards democratizing public services in Indonesia. This research is a qualitative method with a library study approach. The results stated that Indonesia needs to transform public services using the concept of dynamic capabilities in order to realize the democratization of public services.